The Risk-Need-Responsivity Model: How Do Probation Officers Implement the Principles of Effective Intervention? - Viglione, Jill (Criminal justice and behavior, 2019)
The advancement of evidence-based practices (EBP) and the Risk-Need-Responsivity (RNR) model suggests several key practices for probation agencies, including validated risk and needs assessments and appropriate treatment matching. Despite evidence supporting use of practices aligned with the RNR model to improve offender outcomes, research identifies significant implementation challenges in probation practice. Using 1,084 hours of ethnographic data, the current study sought to examine how probation staff implemented best practices aligned with the risk, need, and responsivity principles. Analyses suggest probation staff supervision practices misaligned with research evidence on RNR and associated agency trainings. Probation officers rarely used the risk and needs assessment to inform supervision decisions, creation of case plans, and referrals to treatment programs. Findings highlight the challenges associated with moving evidence on the RNR model to routine probation practice. Implications for policy and research are discussed, including a focus on perceived liability and implementation of best practices.